Pea leaf mitochondrial pyruvate dehydrogenase complex is inactivated in vivo in a light-dependent manner. - Budde, R J (1990)
We examined the effect of light on the activity of the mitochondrial pyruvate dehydrogenase complex (mt-PDC) by using intact green pea (Pisum sativum) seedlings. Upon illumination there is an initial drop in mtPDC activity followed by oscillations that dampen during the initial period of photosynthesis to a steady-state level of one-fourth or less of the mtPDC activity measured in the dark. The initial light-dependent decrease in mtPDC activity is inhibited by 3-(3,4-dichlorophenyl)-1,1-dimethylurea (an inhibitor of photosystem II of photosynthesis) and does not occur in etiolated seedlings. Therefore, the effect of light is indirect and most likely associated with photosynthesis and/or photorespiration. Conditions that would be unfavorable for photorespiration also inhibited the light-dependent decrease in mtPDC activity.